2017
DOI: 10.1183/23120541.00011-2017
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin vivofunctional residual capacity comparisons between multiple-breath nitrogen washout devices

Abstract: Functional residual capacity (FRC) accuracy is essential for deriving multiple-breath nitrogen washout (MBNW) indices, and is the basis for device validation. Few studies have compared existing MBNW devices. We evaluated in vitro and in vivo FRC using two commercial MBNW devices, the Exhalyzer D (EM) and the EasyOne Pro LAB (ndd), and an in-house device (Woolcock in-house device, WIMR).FRC measurements were performed using a novel syringe-based lung model and in adults (20 healthy and nine with asthma), follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Previous studies reporting differences between SF 6 and N 2 LCI (11,12) used different breathing assemblies, breathing patterns, and software algorithms. Even when using the same device for N 2 -MBW, there are differences noted with different software versions (20). The magnitude of differences we observed in our study is similar to differences observed by other investigators.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies reporting differences between SF 6 and N 2 LCI (11,12) used different breathing assemblies, breathing patterns, and software algorithms. Even when using the same device for N 2 -MBW, there are differences noted with different software versions (20). The magnitude of differences we observed in our study is similar to differences observed by other investigators.…”
Section: Discussionsupporting
confidence: 83%
“…A number of studies have identified differences between LCI derived from these two different techniques (11,12) and between different devices using the same technique (20). None of these studies obtained truly simultaneous measurements; results could be influenced by differences in breathing assemblies, subject breathing pattern, and software algorithms used to analyze data.…”
Section: -Mbw)]mentioning
confidence: 99%
“…We studied 27 non-smoking, healthy volunteers (22 at the RNSH site, 5 at the WIMR site) with a median age of 34 (range 19–65) years and spirometry/lung volumes within the limits of normal ( table 1 ). Since MBNW parameters are likely to be device- and protocol-specific [ 17 , 18 ], we were unable to compare all measurements to a single set of reference equations. However, MBNW indices from the free breathing protocol were within the ranges of normal derived from the same testing device ( supplementary table S1 ) [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…However the between-session coefficient of repeatability (equal to 1.96× sd of the mean differences) of LCI, S cond and S acin was greater in our study, which may reflect the different time between sessions (weeks/months versus days). There is a paucity of repeatability data in health, and previous reports may not be generalisable due to persistent between-device differences [ 17 , 18 , 26 ]. Nevertheless, the excellent between-session repeatability for FRC and LCI [ 25 , 27 29 ] but poor repeatability in S acin and S cond [ 25 , 28 ] has been noted with the free breathing protocol by other investigators, regardless of device, tracer gas or disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation